Pembangunan perisian pengajaran dan pembelajaran Multimedia Interaktif Sains - Ibrahim Mohamad, Md. Saad Mohd. Nazri, Mohamad Yatim Maizatul Hayati, Johan Rasyidi, Teh Hui Ping, (Universiti Pendidikan Sultan Idris, 2003)
Pembangunan perisian pengajaran dan pembelajaran Multimedia Interaktif Sains by Ibrahim Mohamad, Md. Saad Mohd. Nazri, Mohamad Yatim Maizatul Hayati, Johan Rasyidi, Teh Hui Ping,